Heat-conducting gel with high heat conductivity and high-temperature aging resistance and preparation method thereof

By adopting a combination solution of zinc oxide and alumina in the thermal gel, and using aluminate coupling agent and chalone and other components, the problem of poor aging hardness and thermal conductivity of thermal conductivity in high-temperature environments is solved, and the effect of high thermal conductivity and high-temperature aging resistance is achieved.

CN119799009AActive Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510001227.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing thermal conductivity gel has aging hardness in high temperature environments and has poor thermal conductivity, making it difficult to meet the heat dissipation needs of high-package and high-power density electronic devices.

Method used

A thermal conductivity gel with high thermal conductivity and high temperature aging resistance was developed. By using a combination scheme of thermal conductivity powders such as zinc oxide and alumina, combined with aluminate coupling agent as a surface modifier and chalone as an anti-aging additive, the thixotropy and thermal conductivity of the gel are improved.

Benefits of technology

It significantly improves the thermal conductivity and thixotropy of the thermal gel, improves the constructionability and high-temperature aging stability, and is suitable for application scenarios with high heat dissipation and high stability requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225234840000131
    Figure BDA0005225234840000131
  • Figure BDA0005225234840000141
    Figure BDA0005225234840000141
  • Figure FDA0005225234830000011
    Figure FDA0005225234830000011
Patent Text Reader

Abstract

The invention relates to heat-conducting gel with high heat conductivity and high-temperature aging resistance and a preparation method thereof.The heat-conducting gel is two-component gel and comprises a component A and a component B. The component A comprises vinyl silicone oil, heat-conducting powder, a surface modifier, an anti-aging additive and a catalyst; the component B comprises vinyl silicone oil, heat-conducting powder, a surface modifier, hydrogen-containing silicone oil and an inhibitor; wherein the heat-conducting powder is one or more of aluminum oxide, silica powder, magnesium oxide, zinc oxide, aluminum nitride, silicon nitride and carbon nanotubes (CNTs); the particle size of the heat-conducting powder is less than or equal to 40 microns. According to the heat-conducting gel, the thixotropy of a product is improved while high heat conductivity of the product is ensured, and the constructability of the product is improved. The heat-dissipating agent has the advantages of low system viscosity, aging stability at high temperature and the like, is suitable for application scenes with high heat-dissipating and aging stability requirements, and can remarkably improve the heat-dissipating effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a thermally conductive gel with high thermal conductivity and high temperature aging resistance, belonging to the field of organic silicon thermally conductive gels. Background Art

[0002] As the performance requirements of high-performance electronic devices become higher and higher, the high packaging and high power density components of modern electronic devices inevitably lead to thermal failures. Effective heat dissipation has become a key technology that affects the life and performance of electronic devices. Thermal interface materials are the best choice to help solve the heat dissipation problem. Thermal interface materials are divided into thermal conductive gels, thermal conductive pads, thermal conductive pastes, thermal conductive phase change and other forms. Thermal conductive gels are curable thermal conductive pastes and dispensable thermal conductive pads. They have the advantages of easy operation and low interface contact thermal resistance. They are considered to be materials that meet the development needs of future thermal interface materials and have received widespread attention from the domestic and foreign industry.

[0003] Compared with thermal conductive gel, thermal conductive gasket is a cured film, which forms a heat conduction channel through extrusion between the heat-generating component and the heat-dissipating component. Since the adhesion between the gasket and the surface of the heat-generating component is very weak, the contact thermal resistance increases, and the thermal conductivity effect becomes worse under the same thermal conductivity. Thermal conductive paste is a non-curing paste-like thermal conductive material. During use, the silicone oil will continue to evaporate, and finally lead to dry powder phenomenon. Thermal conductive phase change material will have a certain fluidity under high temperature, causing the phase change material to overflow at the edge, affecting the thermal conductivity effect.

[0004] Therefore, it is very necessary to develop a thermally conductive gel with high thermal conductivity and high temperature aging resistance. Patent CN201710619110.6 proposes a two-component thermally conductive gel and its preparation method, but the colloid has low thixotropy and flowability, which is not conducive to in-situ curing after dispensing. Patent CN 202010151850.7 proposes a curable two-component thermally conductive heat storage silicone gel, which has a certain heat storage capacity under high temperature conditions, but when used in a high temperature environment for a long time, the problem of aging hardness climbing is inevitable. Summary of the invention

[0005] In view of the current demand for high thermal conductivity of electronic components such as automobiles and electronic devices, the present invention has developed a high thermal conductivity, high temperature aging resistant thermal conductive gel and its preparation method, which improves the thixotropy of the product and the workability of the product while ensuring the high thermal conductivity of the product. It has the advantages of low system viscosity and aging stability at high temperatures. The thermal conductive gel is suitable for application scenarios with high requirements for heat dissipation and aging stability, and can significantly improve the heat dissipation effect.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a thermally conductive gel with high thermal conductivity and high temperature aging resistance, comprising a component A and a component B, wherein the mass ratio of the component A to the component B is 1:0.5 to 2, for example, 1:0.5, 1:0.7, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, etc.;

[0008] Based on the total weight of component A, it contains the following ingredients in weight percentage:

[0009] Vinyl silicone oil 2-10%, such as 2%, 4%, 6%, 8%, 10%, etc.,

[0010] Polyether modified silicone oil 0.5-2%, such as 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, etc.

[0011] Thermal conductive powder 80-95%, such as 80%, 82%, 85%, 88%, 90%, 92%, 95%, etc.

[0012] Surface modifier 0.5-2%, such as 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, etc.,

[0013] Anti-aging additive 0.2-1%, such as 0.2%, 0.4%, 0.6%, 0.8%, 1%, etc.

[0014] Catalyst 0.5-3%, such as 0.5%, 1%, 2%, 3%, etc.,

[0015] Based on the total weight of component B, it contains the following ingredients in weight percentage:

[0016] Vinyl silicone oil 2-10%, such as 2%, 4%, 6%, 8%, 10%, etc.,

[0017] Thermal conductive powder 80-95%, such as 80%, 82%, 85%, 88%, 90%, 92%, 95%, etc.

[0018] Surface modifier 0.5-2%, such as 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, etc.,

[0019] Silicone oil containing 5-10%, such as 5%, 6%, 7%, 8%, 9%, 10%, etc.

[0020] Inhibitor 0.2-1%, such as 0.2%, 0.5%, 0.8%, 1%, etc.;

[0021] Wherein, the thermally conductive powder is one or more of aluminum oxide, silicon powder, magnesium oxide, zinc oxide, aluminum nitride, silicon nitride, and carbon nanotubes (CNTs); the particle size of the thermally conductive powder is ≤40μm, for example, 0.1μm, 0.5μm, 1μm, 3μm, 5μm, 8μm, 10μm, 15μm, 20μm, 25μm, 30μm, 35μm, 40μm, etc.; specifically, the thermally conductive powders in component A and component B may be the same or different.

[0022] In a specific embodiment, the viscosity of the vinyl silicone oil is 50 to 500 cP, for example, 50 cP, 100 cP, 150 cP, 200 cP, 250 cP, 300 cP, 350 cP, 400 cP, 450 cP, 500 cP, etc.; specifically, the vinyl silicone oils in component A and component B may be the same or different;

[0023] For example, the vinyl silicone oil can be QL-2311VDV50 (50 cP), QL-2311VDV100 (100 cP), QL-200DM200 (250 cP), QL-200DM500 (500 cP), Huangshan Qiangli Chemical Co., Ltd.

[0024] In a specific embodiment, the viscosity of the polyether-modified silicone oil is 20 to 300 cP, such as 20 cP, 50 cP, 100 cP, 150 cP, 200 cP, 250 cP, 300 cP, etc.;

[0025] For example, the polyether-modified silicone oil may be SYLGARD TM OFX-0309(20cP), DOWSIL TM 5562(50cP), XIAMETER TM OFX-5098(250cP), DOWSIL TM 5604(300cP), DOWSIL TM .

[0026] The polyether modified silicone oil described in the present invention is used as a surfactant to evenly disperse the anti-aging aid in the silicone oil system.

[0027] In a specific embodiment, the particle shape of the thermally conductive powder can be spherical, quasi-spherical, flake-shaped, needle-shaped or angular, etc., preferably spherical particles;

[0028] As one preferred solution, the thermal conductive powder is a combination powder of zinc oxide and aluminum oxide; preferably, the combined mass ratio of zinc oxide to aluminum oxide is 1:(2-10), such as 1:2, 1:4, 1:6, 1:8, 1:10, etc.; preferably, the particle size of the zinc oxide is ≤1 μm;

[0029] As one of the preferred solutions, the thermally conductive powder is a compound of at least one of aluminum oxides with a particle size of 1 to 5 μm and at least one of aluminum oxides with a particle size of 10 to 40 μm, and the mass ratio of the two is 1:(1 to 5).

[0030] The thermal conductive powder described in the present invention is used to improve the thixotropy of the product and improve the problem of glue overflow between interfaces during curing. When zinc oxide and zinc oxide are compounded, the effect is more prominent due to the surface effect of zinc oxide, which can significantly improve the thixotropy of the product and improve the construction performance of the product. When alumina with different particle sizes is compounded, the thermal conductivity of the product can be further improved.

[0031] In a specific embodiment, the surface modifier is one or more of an aluminate coupling agent, a silane coupling agent, a titanate coupling agent, an aluminum-titanium coupling agent, and an organic borate coupling agent, preferably one or more of an aluminate coupling agent; specifically, the surface modifiers in component A and component B may be the same or different;

[0032] For example, the surface modifier may be HY-985 (aluminate coupling agent), KH-570 (silane coupling agent), HY-105 (phthalate coupling agent), HY-133 (aluminum-titanium coupling agent), Hangzhou Jessica Chemical Co., Ltd.

[0033] The surface modifier described in the present invention has the effects of surface treatment of thermally conductive powder and activation of surfactant, improving the compatibility and dispersibility of thermally conductive powder such as alumina in silicone oil, making the thermally conductive powder dispersed evenly, and especially when an aluminate coupling agent is selected, it can effectively reduce the viscosity of the system and solve the structural problem during storage.

[0034] In a specific embodiment, the anti-aging agent is a ketone agent, selected from one or more of chalcone, acetoin, raspberry ketone, p-methylacetophenone, and p-methylpropiophenone, preferably chalcone.

[0035] The anti-aging aid described in the present invention mainly acts to bind to the remaining silicon hydrogen groups in the system at high temperature, prevent further reaction and crosslinking with the vinyl in the system, and the hardness of the gel continues to increase after the initial curing, thereby improving the stability of the product under high temperature aging. When ketones such as phenyl chalcone are selected, after reacting with the remaining silicon hydrogen groups, the heat resistance of the resin can be effectively improved, the aging stability of the gel under high temperature can be improved, and the problem of hardening under high temperature aging can be improved.

[0036] In a specific embodiment, the catalyst is selected from one or more of platinum compounds and their complexes, palladium compounds and their complexes, nickel compounds and their complexes, rhodium compounds and their complexes, preferably platinum compounds and their complexes;

[0037] For example, the catalyst may be CSAT-F1 (divinyltetramethyldisiloxane platinum complex), CSAT-F6 (tetravinylcyclotetrasiloxane platinum complex), Suzhou Beiteli Polymer Materials Co., Ltd.

[0038] In a specific embodiment, the hydrogen-containing silicone oil has a viscosity of 10 to 500 cP, such as 10 cP, 50 cP, 100 cP, 150 cP, 200 cP, 250 cP, 300 cP, 350 cP, 400 cP, 450 cP, 500 cP, etc.;

[0039] As one preferred embodiment, the hydrogen-containing silicone oil is one or more of end hydrogen-containing silicone oil with a viscosity of 10 to 50 cP and side hydrogen-containing silicone oil with a viscosity of 10 to 500 cP;

[0040] For example, the hydrogen-containing silicone oil can be CX-350 (10cP end hydrogen-containing silicone oil), CX-350LV (50cP end hydrogen-containing silicone oil), CX-351 (10CP side hydrogen-containing silicone oil), CX-351D (200cP side hydrogen-containing silicone oil), CX-351HLV (500cP side hydrogen-containing silicone oil), Guangzhou Chensi New Material Technology Co., Ltd.

[0041] In a specific embodiment, the inhibitor is one or more of tetramethyltetravinylcyclotetrasiloxane, methylbutynol, ethynylcyclohexanol, tetramethyldivinyldisiloxane, and phenylacetylene.

[0042] In a second aspect, the present invention provides a method for preparing the above-mentioned thermally conductive gel with high thermal conductivity and high temperature aging resistance, which can be prepared by conventional blending methods in the field, specifically, comprising the steps of mixing the raw materials of component A to obtain component A; and mixing the raw materials of component B to obtain component B.

[0043] In a specific embodiment, a method for preparing a high thermal conductivity, high temperature aging resistant thermally conductive gel comprises the following steps:

[0044] (1) Add vinyl silicone oil, polyether modified silicone oil and thermal conductive powder into a stirring kettle and stir, then add a surface modifier, heat to 100-120° C., keep warm, evacuate and stir, then cool to below 40° C., add an anti-aging agent and a catalyst, evacuate and stir, and filter to obtain component A;

[0045] (2) Add vinyl silicone oil and thermal conductive powder into a stirring kettle and stir, then add a surface modifier, heat to 100-120°C, keep warm, evacuate and stir, then cool to below 40°C, add hydrogen-containing silicone oil and inhibitor, evacuate and stir, and filter to obtain component B.

[0046] In addition to the conditions specified in the above-mentioned operating steps, other related operations and process conditions in the preparation method of the present invention, such as the rotation speed, time, vacuum pressure and other operations used in the stirring process, and the devices used therein, can be carried out using the corresponding conventional selections in the art. Technicians can optimize them according to actual needs based on the known processes in the prior art, and there is no particular limitation on this.

[0047] The component A prepared in step (1) and the component B prepared in step (2) are respectively packaged into rubber tubes and sealed for storage, thereby obtaining the thermally conductive gel with high thermal conductivity and high temperature aging resistance of the present invention.

[0048] The thermally conductive gel of the present invention is suitable for application scenarios with high requirements for heat dissipation and stability in use, and can significantly improve the heat dissipation effect.

[0049] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0050] 1. Using zinc oxide, zinc oxide, etc. as thermal conductive powder improves the thixotropy of the product and improves the problem of glue overflow between interfaces during curing; at the same time, the compounding of multiple thermal conductive powders with different particle sizes improves the thermal conductivity of the product.

[0051] 2. Aluminate coupling agents are used as surface modifiers to improve the interfacial compatibility between thermal conductive powder and silicone oil, so that the thermal conductive powder can be evenly dispersed, the viscosity of the system is reduced, and the structural problem during storage is solved.

[0052] 3. Add ketones such as chalcone as anti-aging agents. Under high temperature environment, they combine with the remaining silicon hydrogen groups in the system to prevent further reaction and cross-linking with the vinyl in the system. The hardness of the product continues to increase, and the high-temperature aging stability of the product is improved. At the same time, anti-aging agents containing phenyl can improve the heat resistance of the product. DETAILED DESCRIPTION

[0053] For ease of understanding of the present invention, preferred embodiments of the present invention are provided below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. The examples cited are only used to explain the present invention and are not used to limit the scope of the present invention.

[0054] In the embodiments and comparative examples of the present invention, the sources of the main raw materials used are as follows. Unless otherwise specified, other raw materials and reagents were purchased from commercial sources:

[0055] Vinyl silicone oil: QL-2311VDV50 (50cP), QL-2311VDV100 (100cP), QL-200DM200 (250cP), QL-200DM500 (500cP), Huangshan Qiangli Chemical Co., Ltd.

[0056] Polyether modified silicone oil: SYLGARD TM OFX-0309(20cP), DOWSIL TM 5562(50cP), XIAMETER TM OFX-5098(250cP), DOWSIL TM 5604(300cP), Dow Chemical Company;

[0057] Quasi-spherical zinc oxide: Z-65 (0.5 μm), Z-80 (1 μm), Changzhou Boyang New Material Technology Co., Ltd.; ZnO908 (5 μm), Jiangsu Haichuang Zinc Industry Technology Co., Ltd.;

[0058] Spherical alumina: NAS005 (0.5μm), NA1010W (1μm), NA1050 (5μm), Jiangsu Lianrui New Materials Co., Ltd.; BAK-10 (10μm), BAK-40 (40μm), Ya'an Baitu High-tech Materials Co., Ltd.;

[0059] Other thermal conductive powders: YTA-5 (5μm aluminum hydroxide), YTM-1 (1μm magnesium hydroxide), YTM-8 (10μm magnesium hydroxide), Jinan Jinyingtai Chemical Co., Ltd.

[0060] Surface modifier: HY-985 (aluminate coupling agent), HY-105 (phthalate coupling agent), Hangzhou Jessica Chemical Co., Ltd.;

[0061] Chalcone: H832838 (2-hydroxychalcone), F859937 (4'-fluorochalcone), Tianjin Xidian Chemical Technology Co., Ltd.;

[0062] Platinum catalyst: CSAT-F1 (divinyltetramethyldisiloxane platinum complex), CSAT-F6 (tetravinylcyclotetrasiloxane platinum complex), Suzhou Bettery Polymer Materials Co., Ltd.;

[0063] Hydrogenated silicone oil: CX-350 (hydrogenated silicone oil at 10cP end), CX-350LV (hydrogenated silicone oil at 50cP end), CX-351 (hydrogenated silicone oil at 10CP side), CX-351D (hydrogenated silicone oil at 200cP side), CX-351H (hydrogenated silicone oil at 500cP side), Guangzhou Chensi New Material Technology Co., Ltd.

[0064] Inhibitors: YZJ-1 (ethynyl cyclohexanol), YZJ-3 (tetramethyltetravinylcyclotetrasiloxane), Guangzhou Siyou New Material Technology Co., Ltd.

[0065] Example 1

[0066] 505g of 50cp vinyl silicone oil, 51g of 300cp polyether-modified silicone oil, 3034g of 0.5μm quasi-spherical zinc oxide, 3033g of 5μm spherical alumina, and 3033g of 40μm spherical alumina were added into a double planetary stirring kettle at a stirring speed of 20rpm / min and a dispersion speed of 600rpm / min. 51g of aluminate coupling agent was then added, heated to 120°C, kept warm, and stirred under vacuum for 2h. The mixture was then cooled to below 40°C, 22g of 2-hydroxychalcone and 271g of divinyltetramethyldisiloxane platinum complex were added, the stirring speed was 20rpm / min, the dispersion speed was 600rpm / min, the mixture was stirred under vacuum for 15min, and filtered through a 100-mesh filter to obtain component A.

[0067] 205g of 50cp vinyl silicone oil, 3034g of 0.5μm quasi-spherical zinc oxide, 3033g of 5μm spherical alumina, and 3033g of 40μm spherical alumina were added into a double planetary stirring kettle, with a stirring speed of 20rpm / min and a dispersion speed of 600rpm / min, and then 173g of aluminate coupling agent was added, heated to 120°C, kept warm, and stirred under vacuum for 2h, then cooled to below 40°C, 476g of 10cP end hydrogen-containing silicone oil, 26g of 10cP side hydrogen-containing silicone oil, and 20g of ethynyl cyclohexanol were added, with a stirring speed of 20rpm / min and a dispersion speed of 600rpm / min, and stirred under vacuum for 15min, and filtered through a 100-mesh filter to obtain component B;

[0068] The components A and B are respectively packed into rubber tubes and sealed for storage to obtain Example Sample 1. When in use, the components A and B are combined in a desired mass ratio.

[0069] Example 2

[0070] 460g of 100cp vinyl silicone oil, 198g of 250cp polyether-modified silicone oil, 828g of 1μm quasi-spherical zinc oxide, 1378g of 1μm spherical alumina, and 6894g of 10μm spherical alumina were added into a double planetary stirring kettle, with a stirring speed of 20rpm / min and a dispersion speed of 600rpm / min, and then 94g of phthalate coupling agent was added, heated to 120°C, kept warm, and stirred under vacuum for 2h, then cooled to below 40°C, 95g of 4'-fluorochalcone and 53g of tetravinylcyclotetrasiloxane platinum complex were added, the stirring speed was 20rpm / min, the dispersion speed was 600rpm / min, and the mixture was stirred under vacuum for 15min, and filtered through a 100-mesh filter to obtain component A;

[0071] 236g of 100cp vinyl silicone oil, 828g of 1μm quasi-spherical zinc oxide, 1378g of 1μm spherical alumina, and 6894g of 10μm spherical alumina were added into a double planetary stirring kettle, with a stirring speed of 20rpm / min and a dispersion speed of 600rpm / min, and then 54g of phthalate coupling agent was added, heated to 120°C, kept warm, and stirred under vacuum for 2h, then cooled to below 40°C, 468g of 10cP end hydrogen-containing silicone oil, 48g of 200cP side hydrogen-containing silicone oil, and 94g of tetramethyltetravinylcyclotetrasiloxane were added, with a stirring speed of 20rpm / min and a dispersion speed of 600rpm / min, and stirred under vacuum for 15min, and filtered through a 100-mesh filter to obtain component B;

[0072] The A component and the B component are respectively packed into rubber tubes and sealed for storage to obtain Example Sample 2.

[0073] Example 3

[0074] 207g of 250cp vinyl silicone oil, 57g of 50cp polyether-modified silicone oil, 4720g of 1μm spherical alumina and 4720g of 10μm spherical alumina were added into a double planetary stirring kettle, the stirring speed was 20rpm / min, the dispersion speed was 600rpm / min, 194g of aluminate coupling agent was added, the mixture was heated to 120°C, the mixture was kept warm, and the mixture was stirred under vacuum for 2h, then the mixture was cooled to below 40°C, 34g of 2-hydroxychalcone and 68g of divinyltetramethyldisiloxane platinum complex were added, the stirring speed was 20rpm / min, the dispersion speed was 600rpm / min, the mixture was stirred under vacuum for 15min, and the mixture was filtered through a 100-mesh filter to obtain component A;

[0075] 984 g of 250 cp vinyl silicone oil, 4020 g of 1 μm spherical alumina, and 4020 g of 10 μm spherical alumina were added into a double planetary stirring kettle, with a stirring speed of 20 rpm / min and a dispersion speed of 600 rpm / min. 52 g of aluminate coupling agent was then added, heated to 120° C., kept warm, and stirred under vacuum for 2 h. The temperature was then lowered to below 40° C., 818 g of 50 cP end hydrogen-containing silicone oil, 64 g of 200 cP side hydrogen-containing silicone oil, and 42 g of ethynyl cyclohexanol were added, with a stirring speed of 20 rpm / min and a dispersion speed of 600 rpm / min, and stirred under vacuum for 15 min. The mixture was filtered through a 100-mesh filter to obtain component B.

[0076] The A component and the B component are respectively packed into rubber tubes and sealed for storage to obtain Example Sample 3.

[0077] Example 4

[0078] 992 g of 500 cp vinyl silicone oil, 186 g of 20 cp polyether modified silicone oil, and 8270 g of 5 μm spherical alumina were added into a double planetary stirring kettle, with a stirring speed of 20 rpm / min and a dispersion speed of 600 rpm / min. 181 g of phthalate coupling agent was added, heated to 120° C., kept warm, and stirred under vacuum for 2 h. The mixture was then cooled to below 40° C., 82 g of 4'-fluorochalcone and 289 g of tetravinylcyclotetrasiloxane platinum complex were added, with a stirring speed of 20 rpm / min and a dispersion speed of 600 rpm / min. The mixture was stirred under vacuum for 15 min, and filtered through a 100-mesh filter to obtain component A.

[0079] 524 g of 500 cp vinyl silicone oil and 8360 g of 5 μm spherical alumina were added into a double planetary stirring kettle, with a stirring speed of 20 rpm / min and a dispersion speed of 600 rpm / min. 58 g of phthalate coupling agent was added, heated to 120° C., kept warm, and stirred under vacuum for 2 h. The mixture was then cooled to below 40° C., 887 g of 50 cP end hydrogen-containing silicone oil, 96 g of 500 cP side hydrogen-containing silicone oil, and 75 g of tetramethyltetravinylcyclotetrasiloxane were added, with a stirring speed of 20 rpm / min and a dispersion speed of 600 rpm / min, and stirred under vacuum for 15 min. The mixture was filtered through a 100-mesh filter to obtain component B.

[0080] The A component and the B component are respectively packed into rubber tubes and sealed for storage to obtain Example Sample 4.

[0081] Comparative Example 1

[0082] Component A and component B were prepared according to the preparation method of Example 1, except that the spherical alumina with a particle size of 5 μm in component A and component B were replaced with aluminum hydroxide with a particle size of 5 μm of the same mass, and other operations and conditions remained unchanged.

[0083] The A component and the B component are respectively packed into rubber tubes and sealed for storage to obtain comparative sample 1.

[0084] Comparative Example 2

[0085] The preparation method of Example 2 is followed, except that in component A and component B, the spherical alumina with a particle size of 1 μm is replaced by an equal mass of magnesium hydroxide with a particle size of 1 μm, and the spherical alumina with a particle size of 10 μm is replaced by an equal mass of magnesium hydroxide with a particle size of 10 μm, and other operations and conditions remain unchanged, to obtain component A and component B.

[0086] The A component and the B component are respectively packed into rubber tubes and sealed for storage to obtain comparative sample 2.

[0087] Comparative Example 3

[0088] The preparation method of Example 1 is followed, except that in component A and component B, the spherical zinc oxide with a particle size of 0.5 μm is replaced by an equal mass of zinc oxide with a particle size of 5 μm, and the spherical aluminum oxide with a particle size of 5 μm is replaced by an equal mass of aluminum hydroxide with a particle size of 5 μm, and other operations and conditions remain unchanged, to obtain component A and component B.

[0089] The A component and the B component are respectively packed into rubber tubes and sealed for storage to obtain comparative sample 2.

[0090] Comparative Example 4

[0091] The preparation method of Example 3 is followed, except that in component A and component B, the spherical alumina with a particle size of 1 μm is replaced by an equal mass of magnesium hydroxide with a particle size of 1 μm, and the spherical alumina with a particle size of 10 μm is replaced by an equal mass of magnesium hydroxide with a particle size of 10 μm, and other operations and conditions remain unchanged, to obtain component A and component B.

[0092] The A component and the B component are respectively packed into rubber tubes and sealed for storage to obtain comparative sample 2.

[0093] Comparative Example 5

[0094] The preparation method of Example 1 is followed, except that no surface modifier is added to component A and component B after adding the thermal conductive powder, and other operations and conditions remain unchanged, to obtain component A and component B.

[0095] The A component and the B component are respectively packed into rubber tubes and sealed for storage to obtain comparative sample 2.

[0096] Comparative Example 6

[0097] Component A and component B were prepared according to the preparation method of Example 1, except that no anti-aging agent was added to component A, and other operations and conditions remained unchanged.

[0098] The A component and the B component are respectively packed into rubber tubes and sealed for storage to obtain comparative sample 2.

[0099] Comparative Example 7

[0100] Component A and component B were prepared according to the preparation method of Example 1, except that the particle size of the thermal conductive powder (quasi-spherical zinc oxide, spherical aluminum oxide) in component A and component B was replaced with 45 μm, and other operations and conditions remained unchanged.

[0101] The A component and the B component are respectively packed into rubber tubes and sealed for storage to obtain comparative sample 1.

[0102] The thermally conductive gels prepared in Examples 1-4 and Comparative Examples 1-7 were subjected to performance tests:

[0103] The thermally conductive gels prepared in the above embodiments and comparative examples were heated in an oven at 60°C for 30 minutes to prepare fully cured sample blocks. The thermal conductivity of each sample block was tested at the same temperature and humidity (temperature 25±2°C, humidity 50±5%RH). At the same time, the initial viscosity of the thermally conductive gels prepared in the embodiments and comparative examples at different rotation speeds after the A and B components were mixed at a mass ratio of 1:1 was tested, and the thixotropic value was calculated. The relevant comparison results are shown in Tables 1 and 2 below:

[0104] Thermal conductivity and hardness test method: Mix and stir the A and B components of the thermal conductive gel evenly, then evacuate and remove bubbles. Heat in a 60°C oven to obtain a cured product. Cut the test samples into specified sizes according to GB / T531-1999 and test the Shore 00 hardness. Cut the samples into test samples of specified sizes according to ASTMD5470 and test them to obtain the thermal conductivity.

[0105] Viscosity and thixotropy test method: According to GB / T2794-1995, the viscosity values ​​of components A and B in the thermal conductive gel at 0.1rpm and 1rpm and the viscosity values ​​of components A and B in the thermal conductive gel prepared in each embodiment and comparative example after being mixed uniformly in a mass ratio of 1:1 at 25°C were tested respectively, and the ratio of the viscosity at 0.1rpm to the viscosity at 1rpm was defined as the thixotropy value.

[0106] Structural test method: Pour 3cm thick thermal conductive gel of components A and B into a cylindrical sample tank with a diameter of 5cm. Test the cone penetration after 30 days according to GB / T269-91. When the cone penetration is less than 20mm, it is judged that structuring occurs.

[0107] High temperature aging test method: Cut the test sample into the specified size according to GB / T531-1999, put the sample into ESPEC GPH-20 oven, heat it at 150℃ for 1000h to test Shore 00 hardness.

[0108] Table 1 Comparison of viscosity and thermal conductivity of thermally conductive gels prepared in Examples and Comparative Examples

[0109]

[0110] Table 2 Comparison of the structure and high temperature aging of the thermally conductive gels prepared in the examples and comparative examples

[0111]

[0112] From the comparison of the performance data of the thermally conductive gel of the above embodiments and comparative examples: when other conditions are the same, it can be found from the comparison of embodiments 1, 2, 3, and 4 that the preferred solution of zinc oxide and aluminum oxide has lower viscosity and higher thixotropy; by comparing embodiments 1, 2, and 3 with comparative examples 1, 2, and 4, the thermal conductivity of the composite solution of aluminum oxide and zinc oxide is significantly higher than that of the composite solution of other thermally conductive powders; by comparing embodiment 1 with comparative example 3, when the minimum powder particle size is ≤1 μm, the thixotropy of the product can be effectively improved to prevent the loss of glue before curing; by comparing embodiment 1 with comparative example 7, when the maximum particle size of spherical aluminum oxide is greater than 40 μm, the particle size arrangement changes, resulting in increased viscosity, decreased thixotropy and thermal conductivity, and the overall performance is not as good as the preferred solution.

[0113] Compared with Example 5 without adding any surface modifier, Example 1 with surface modification by aluminate coupling agent has lower viscosity and no structuring problem during subsequent storage. Adding the surface modifier aluminate coupling agent plays a role in reducing viscosity and preventing storage structuring. Compared with Example 6 without adding any anti-aging agent, Example 1 adds chalcone as an anti-aging agent. The hardness of the high-temperature aging at 150°C@1000h is almost unchanged. The addition of chalcone effectively improves the stability of the thermal conductive gel after curing during high-temperature aging.

[0114] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A thermally conductive gel with high thermal conductivity and high temperature aging resistance, characterized in that: It comprises component A and component B, wherein the mass ratio of component A to component B is 1:0.5-2; Based on the total weight of component A, it contains the following ingredients in weight percentage: Based on the total weight of component B, it contains the following ingredients in weight percentage: Wherein, the thermally conductive powder is one or more of aluminum oxide, silicon powder, magnesium oxide, zinc oxide, aluminum nitride, silicon nitride, and carbon nanotubes; and the particle size of the thermally conductive powder is ≤40 μm.

2. The thermally conductive gel according to claim 1, characterized in that: The viscosity of the vinyl silicone oil is 50 to 500 cP.

3. The thermally conductive gel according to claim 1, characterized in that: The viscosity of the polyether modified silicone oil is 20 to 300 cP.

4. The thermally conductive gel according to claim 1, characterized in that: The particle shape of the thermally conductive powder can be spherical, quasi-spherical, flake, needle-shaped or angular, preferably spherical particles; Preferably, the thermally conductive powder is a combination powder of zinc oxide and aluminum oxide; preferably, the combined mass ratio of zinc oxide to aluminum oxide is 1:(2-10); preferably, the particle size of the zinc oxide is ≤1 μm; Preferably, the thermally conductive powder is a compound of at least one of aluminum oxides with a particle size of 1 to 5 μm and at least one of aluminum oxides with a particle size of 10 to 40 μm, and the mass ratio of the two is 1:(1 to 5).

5. The thermally conductive gel according to claim 1, characterized in that: The surface modifier is one or more of an aluminate coupling agent, a silane coupling agent, a titanate coupling agent, an aluminum-titanium coupling agent, and an organic borate coupling agent, preferably one or more of an aluminate coupling agent.

6. The thermally conductive gel according to claim 1, characterized in that: The anti-aging auxiliary agent is a ketone auxiliary agent, selected from one or more of chalcone, acetoin, raspberry ketone, p-methylacetophenone, and p-methylpropiophenone, preferably chalcone.

7. The thermally conductive gel according to claim 1, characterized in that: The catalyst is selected from one or more of platinum compounds and their complexes, palladium compounds and their complexes, nickel compounds and their complexes, rhodium compounds and their complexes, preferably platinum compounds and their complexes.

8. The thermally conductive gel according to claim 1, characterized in that: The hydrogen-containing silicone oil has a viscosity of 10 to 500 cP; Preferably, the hydrogen-containing silicone oil is one or more of end hydrogen-containing silicone oil with a viscosity of 10 to 50 cP and side hydrogen-containing silicone oil with a viscosity of 10 to 500 cP.

9. The thermally conductive gel according to claim 1, characterized in that: The inhibitor is one or more of tetramethyltetravinylcyclotetrasiloxane, methylbutynol, ethynylcyclohexanol, tetramethyldivinyldisiloxane, and phenylacetylene.

10. A method for preparing the high thermal conductivity and high temperature aging resistant thermal conductive gel according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) Add vinyl silicone oil, polyether modified silicone oil and thermal conductive powder into a stirring kettle and stir, then add a surface modifier, heat to 100-120° C., keep warm, evacuate and stir, then cool to below 40° C., add an anti-aging agent and a catalyst, evacuate and stir, and filter to obtain component A; (2) Add vinyl silicone oil and thermal conductive powder into a stirring kettle and stir, then add a surface modifier, heat to 100-120°C, keep warm, evacuate and stir, then cool to below 40°C, add hydrogen-containing silicone oil and inhibitor, evacuate and stir, and filter to obtain component B.

Citation Information

Patent Citations

  • Heat-conducting silica gel composition and preparation method thereof

    CN107043541A

  • Addition-type double-component organic silicon heat-conduction gel and preparation method thereof

    CN108504108A

  • Special silica gel with high coefficient of thermal conductivity for electronic industries and preparation method thereof

    CN109593366A

  • Thermally-stable two-component heat-conducting gel and preparation method thereof

    CN115216154A

  • Heat-conducting gel with high heat conductivity and high aging resistance and preparation method of heat-conducting gel

    CN116410569A